SPLIT DUCT AC LEAKAGE MONITORING SYSTEM VIA GOOGLE SHEETS - Cahyo , Chandra Darmawan Dwi; Jamaaluddin, Jamaaluddin (Journal for Technology and Science, 2024)
General Background: Split duct air conditioners are prone to leaks, often resulting from corrosion in water catchment systems, which can lead to significant operational hazards such as electrical fires. Specific Background: Given the prevalence of these issues, there is an urgent need for effective monitoring solutions to maintain optimal air conditioner performance and prevent leaks. Knowledge Gap: Current monitoring systems lack integration with real-time data reporting mechanisms that can alert users promptly to potential issues. Aims: This research aims to develop a monitoring device utilizing NodeMCU ESP8266, water level sensors, and Google Sheets to enable real-time monitoring and management of water levels in split duct air conditioners. Results: The device successfully operates by turning on the fan when water levels are below 2 cm and activating the pump when levels exceed this threshold. The data is continuously sent to Google Sheets, allowing for easy monitoring and management. Novelty: This study presents a novel approach to air conditioner leak monitoring by integrating IoT technology, offering an efficient and user-friendly solution for residents. Implications: The developed monitoring tool significantly enhances the ability to detect and manage potential leaks in real time, thereby improving safety and operational efficiency. Future research should focus on enhancing sensor accuracy through specialized equipment and exploring alternative IoT platforms for improved data visualization, thereby providing users with an even more effective monitoring experience.